Penerapan Technology Acceptance Model (TAM) Dalam Menganalisis Penerimaan Aplikasi E-kinerja Pada Dinas PUPR Kota Gorontalo - Gelo, Siti Zalyah; Amali, Lanto Ningrayati; Polin, Muchlis (Diffusion: Journal of Systems and Information Technology, 2024)
Abstract E-kinerja is an application used as a tool for recording performance and monitoring employee performance. Many agencies have implemented the use of e-kinerja to support work, one of which is the Gorontalo City PUPR Service. However, in practice the implementation of the e-kinerja application at the Gorontalo City PUPR Service has not been carried out optimally. This is proven by the fact that there are still employees who use the e-performance application according to the provisions that have been set, such as not entering their performance on time and some even not filling in their performance in the system. This will affect targets and performance assessments resulting in administrative sanctions up to dismissal. It is not yet known whether the e-Kinerja application has been well received or not by users at the Gorontalo City PUPR Service. This research was conducted to find out how far the E-Kinerja application has been received at the Gorontalo City PUPR Service and what factors can influence user acceptance. . This research uses descriptive quantitative methods and uses the TAM Model to measure user acceptance. The analysis results show that the e-kinerja application has been well received by users with acceptance of 89%.